C.E. Credit. Aging and Endodontics: A Narrative Review to Guide Case Selection and Treatment - Yaara Berdan; Elisa M. Chávez (Taylor & Francis Group, 2023)
ABSTRACTBackground Understanding the implications of aging on endodontic treatment is important to appropriately care for patients with increasingly complex and diverse health needs in conjunction with increasingly intact and complex dentition.Types of Studies Reviewed Content from existing studies and literature on aging, oral health and endodontics was reviewed and integrated to present a holistic approach to endodontics for older adults. The full spectrum of need and ability of older adults, from well to frail elders, was taken into consideration.Results Age-related changes in the dentition present challenges to endodontic diagnosis and treatment that are compounded by physical or cognitive impairments that alter presentation of disease and response to treatment. Communication may need to extend beyond the patient and the referring provider to establish a diagnosis, clear expectations and goals of treatment.Practical Implications It is important to understand the complexities unique to aging and aging's potential impact on clinical outcomes to ensure the appropriate inclusion and delivery of endodontic care to older adults.Continuing Education Credit Available The practice worksheet is available online in the supplementary material tab for this article. A CDA Continuing Education quiz is online for this article: https://www.cdapresents360.com/learn/catalog/view/20.